Dataset on Environmental Parameters and Greenhouse Gases in Port and Harbor Seawaters of Jeju Island, Korea - Jae-Hyun Lim; Ju-Hyoung Kim; Hyo-Ryeon Kim; Seo-Young Kim; Il-Nam Kim (Data, 2025)
This dataset presents environmental observations collected in August 2021 from 18 port and harbor sites located around Jeju Island, Korea. It includes physical, biogeochemical, and greenhouse gas (GHG) variables measured in surface seawater, such as temperature, salinity, dissolved oxygen, nutrients, chlorophyll-a, pH, total alkalinity, and dissolved inorganic carbon. Concentrations and air–sea fluxes of nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2) were also quantified. All measurements were conducted following standardized analytical protocols, and certified reference materials and duplicate analyses were used to ensure data accuracy. Consequently, the dataset revealed that elevated nutrient accumulation in port and harbor waters and GHG concentrations tended to be higher at sites with stronger land-based influence. During August 2021, most sites functioned as sources of N2O, CH4, and CO2 to the atmosphere. This integrated dataset offers valuable insights into the influence of anthropogenic and hydrological factors on coastal GHG dynamics and provides a foundation for future studies across diverse semi-enclosed marine systems.